Uncertainty’s impact on adaptive performance in the post-COVID era: The moderating role of perceived leader’s effectiveness - Junça Silva, A.; Caetano, A. (BRQ Business Research Quarterly, 2024)
This study builds upon existing research on daily adaptive performance by focusing on two main aspects: (1) the fluctuations within individuals concerning uncertainty in relation to daily negative affect and daily adaptive performance and (2) the variations between individuals in the perceived effectiveness of their leaders as a relevant boundary condition of these relationships. Data were gathered during a post-COVID phase from a sample of 176 Portuguese working adults, for 10 days, resulting in a total of 1,760 measurement occasions. The results of the multilevel analysis revealed a positive correlation between fluctuations in daily uncertainty and daily negative affect. Notably, this relationship was influenced by the perceived effectiveness of leaders. Specifically, the presence of an effective leader mitigated the heightened negative affect caused by increased uncertainty. In addition, the findings demonstrated a positive link between daily negative affect and daily adaptive performance. Moreover, a statistically significant indirect effect was observed, indicating that uncertainty led to fluctuations in adaptive performance through its impact on daily negative affect. Essentially, higher levels of uncertainty contributed to increased negative affect among employees, subsequently influencing their daily adaptive performance. It is important to note that this pathway was further influenced by the perceived effectiveness of leaders. In cases where employees perceived their leaders as less effective, the connection between negative affect and adaptive performance was more pronounced. This study underscores the significance of perceived effective leadership, particularly in unique contexts such as the post-COVID era: an effective leader is always good for affective regulation, but a less effective leader is not always bad regarding adaptive performance. This complexity prompts discussions on implications for both theoretical understanding and practical application.